Growth of Scenedesmus dimorphus in swine wastewater with versus without solid–liquid separation pretreatment. (February 2023) - Osabutey, Augustina; Haleem, Noor; Uguz, Seyit; Min, Kyungnan; Samuel, Ryan; Albert, Karlee; Anderson, Gary; Yang, Xufei
Graphical abstract: Highlights: Solids and nutrients in raw swine wastewater were removed with 3-step pretreatment. Better S. dimorphus growth was achieved in pretreated than raw swine wastewater. Algal reactors showed no consistent wastewater treatment boost versus control. Algae-rich solids harvested from pretreated wastewater contained 5.7% nitrogen. S. dimorphus is unlikely a suitable microalgal species for phosphorus recovery. Abstract: Scenedesmus dimorphus was cultivated in raw and pretreated swine wastewater (SW) with 6-L photobioreactors (PBRs) to investigate the effect of solid–liquid separation on algal growth. The same aerated PBRs containing no algae were used as control. Moderate COD and nitrogen removal from the SW was achieved with the algal PBRs. However, compared to the control reactors, they offered no consistent treatment boost. Improved algal growth occurred in the pretreated SW, as measured by maximum algal cell count (3202 ± 275 × 10 6 versus 2286 ± 589 × 10 6 cells L −1 ) and cell size. The enhanced algal growth in the pretreated SW resulted in relatively high nitrogen (5.7 %) and organic matter contents in the solids harvested at the end of cultivation experiments, with ∼25.6 % of nitrogen in the SW retained in the solids and ∼9.1 % absorbed by algae. The pretreatment also resulted in elevated phosphorus removal. This study is anticipated to foster the development of microalgae-based SW treatment processes.